3D Culture as a Clinically Relevant Model for Personalized Medicine. (June 2017) - Fong, Eliza Li Shan; Toh, Tan Boon; Yu, Hanry; Chow, Edward Kai-Hua
Advances in understanding many of the fundamental mechanisms of cancer progression have led to the development of molecular targeted therapies. While molecular targeted therapeutics continue to improve the outcome for cancer patients, tumor heterogeneity among patients, as well as intratumoral heterogeneity, limits the efficacy of these drugs to specific patient subtypes, as well as contributes to relapse. Thus, there is a need for a more personalized approach toward drug development and diagnosis that takes into account the diversity of cancer patients, as well as the complex milieu of tumor cells within a single patient. Three-dimensional (3D) culture systems paired with patient-derived xenografts or patient-derived organoids may provide a more clinically relevant system to address issues presented by personalized or precision medical approaches. In this review, we cover the current methods available for applying 3D culture systems toward personalized cancer research and drug development, as well as key challenges that must be addressed in order to fully realize the potential of 3D patient-derived culture systems for cancer drug development. Greater implementation of 3D patient-derived culture systems in the cancer research field should accelerate the development of truly personalized medical therapies for cancer patients.